Peningkatan Ketrampilan Siswa SMK Kosgoro Kota Bogor dalam Mengisi Suara (Voice Over) Konten Video Kreatif - Annory Langga’o; Valianty Sariswara (Universitas Muhammadiyah Manado, 2023)
Vocational high schools (SMK) are schools that provide basic or provision for students to have skills after graduating according to their field of interest. Because every time a student registers for a vocational school, the first time they immediately choose the major they are interested in. This service was carried out by Pakuan University in collaboration with Kosgoro Vocational School, Bogor City as a partner. Which was held for 3 days from 16, 17 and 18 October 2023. The aim of this competition was to improve the skills of Kosgoro Vocational School students in Bogor City in improving voice acting (voice 0ver) as well as having camera engineering skills to support creative video making. We can see indicators of the success of this service in the number of participants who took part in the service, feedback from questionnaires from participants who took part and discussions with partners with the service team in subsequent activities.